THE EFFECT OF ENVIRONMENT ANDAUDITOR INDIVIDUAL FACTORS ON AUDITOR JUDGMENT - Dianwicaksih Arieftiara; Pujiono Pujiono (Universitas Hayam Wuruk Perbanas, 2013)
This research examinesfactors influence auditors, when they make ortake judgments during audit client’s financial statement. Those factors were divided into two groups; environmental factors and auditor individual factors. Environmental factors are consists of internal auditor quality and communication between auditor and client. Whereas individual factors consist of auditor’s experience and auditor’s attitude under time pressure. Furthermore,this research used empires data are 86 respondents. The characteristic of those respondents were auditors who work in public accounting firms on Surabaya, had experience three years minimum, ever audit client who had internal audit departmentand ever audit the same client morethan once. The results of researches analysis could be learned that there are many factors influencing auditor judgment. In conclusion, this study found that internal auditor quality, auditor’s experience and auditor’s attitude under time pressure has influence toward auditor judgment. Whereas, communication between auditor and client doesn’t have influence toward auditor judgment.